2021
DOI: 10.3390/en14206800
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Self-Cleaning Hydrophobic Nanocoated Photovoltaic Panels in a Dusty Environment

Abstract: The efficiency of a photovoltaic (PV) panels drops significantly in dusty environments. The variation in temperature could have a substantial impact on PV panel cells, which could further lead to high deterioration and eventually permanent damage to the PV material in the presence of dust. To resolve this issue, in this work a novel hydrophobic silicon dioxide (SiO2)-based nanoparticle coating is proposed for the PV panel, to shrink the surface stress developed between the water and the coated facet. Two ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The efficiency of the nanocoated panel was higher than the reference panel by 30.7%. It is found and concluded that the nanocoated panel has greater output power and efficiency compared to the reference panel and the previous studies 13…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The efficiency of the nanocoated panel was higher than the reference panel by 30.7%. It is found and concluded that the nanocoated panel has greater output power and efficiency compared to the reference panel and the previous studies 13…”
Section: Discussionmentioning
confidence: 64%
“…The average electrical efficiency of the coated module is approximately 13.79%, while that of the uncoated module is approximately 13.29%. It was discovered and concluded that coated panels generate 13% more output power even when the surface is not cleaned on a regular basis 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These factors reduce PV panel production and thu kept below specific levels [6,7]. Considering the adverse effect of dust accumu PV panels, there have been significant efforts to discover ways and means to clea panels without ruining their surface [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on anti-sticking surfaces, but many of them focus on the control of surface wettability [4,5]. Micro-and/or nano-surface textures have been obtained to form superhydrophobic surfaces with self-cleaning [6] or anti-icing [7] properties. These surfaces are usually exposed to the atmosphere and are viable at normal temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%